2016
DOI: 10.1242/dev.130492
|View full text |Cite
|
Sign up to set email alerts
|

Re-epithelialization of cutaneous wounds in adult zebrafish uses a combination of mechanisms at play during wound closure in embryonic and adult mammals

Abstract: Re-epithelialization of cutaneous wounds in adult mammals takes days to complete and relies on numerous signalling cues and multiple overlapping cellular processes that take place both within the epidermis and in other participating tissues. Re-epithelialization of partial-or fullthickness skin wounds of adult zebrafish, however, is extremely rapid and largely independent of the other processes of wound healing. Live imaging after treatment with transgene-encoded or chemical inhibitors reveals that re-epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 92 publications
4
81
0
Order By: Relevance
“…This could be considered necessary for the epithelialization to close the wound. Recent scanning electron microscope study (Richardson et al, ) reported that in Danio rerio superficial keratinocytes (=epithelial cells, present study) closer to the wound were strongly elongated in the direction of the wound and suggested that keratinocytes undergo directed and coordinated cell flattening, polarization and elongation. Sonnemann and Bement () reported in a review article that in different vertebrates and invertebrates epidermal cells, in general, near the wound edge undergo a transient dedifferentiation; assume a more flattened, elongate phenotype; and migrate into the wound area.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This could be considered necessary for the epithelialization to close the wound. Recent scanning electron microscope study (Richardson et al, ) reported that in Danio rerio superficial keratinocytes (=epithelial cells, present study) closer to the wound were strongly elongated in the direction of the wound and suggested that keratinocytes undergo directed and coordinated cell flattening, polarization and elongation. Sonnemann and Bement () reported in a review article that in different vertebrates and invertebrates epidermal cells, in general, near the wound edge undergo a transient dedifferentiation; assume a more flattened, elongate phenotype; and migrate into the wound area.…”
Section: Discussionsupporting
confidence: 58%
“…Scanning electron microscope (SEM) provides a means for observing and surveying the surface topography of tissue specimen and is a useful tool to reveal the details of surface architecture of tissues to an extent not possible by other procedures. Studies concerned with the SEM of healing of the skin wound, however, are relatively few (Kumari, Verma, Nigam, Mittal, & Mittal, ; Rai et al, ; Richardson et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is an advantage because certain proteins may play different roles in each phase. For example, Fibroblasts Growth Factors are not required for re-epithelialization, but are required for later epidermal remodeling and granulation tissue formation (Richardson et al, 2016). Generation of a “skinbow” zebrafish in the Poss lab, has allowed large-scale tracking of skin cells response to injury and has enabled the identification of differences in epithelial cellular responses during normal homeostatic turnover of the skin versus minor exfoliation injuries versus regeneration of major portions of the skin.…”
Section: Scar-free Regeneration: Learning From Animals With the Namentioning
confidence: 99%
“…Generation of a “skinbow” zebrafish in the Poss lab, has allowed large-scale tracking of skin cells response to injury and has enabled the identification of differences in epithelial cellular responses during normal homeostatic turnover of the skin versus minor exfoliation injuries versus regeneration of major portions of the skin. Indeed the combination of transgenic zebrafish and in vivo imaging has also facilitated the identification of key roles for β-catenin/integrin signaling in re-epithelialization of full-thickness skin wounds in adult zebrafish (Richardson et al, 2016). …”
Section: Scar-free Regeneration: Learning From Animals With the Namentioning
confidence: 99%
See 1 more Smart Citation